Effect of Turkish Propolis on miRNA Expression, Cell Cycle, and Apoptosis in Human Breast Cancer (MCF-7) Cells. (2nd January 2020) - Misir, Sema; Aliyazicioglu, Yüksel; Demir, Selim; Turan, Ibrahim; Hepokur, Ceylan
Abstract: Enriched in flavonoid compounds, phenol acids, and terpene derivatives, propolis has been shown to regulate apoptosis signaling pathways and alter the expression of microRNAs (miRNAs). In the present study, it has been aimed to examine the effects of Turkish propolis on miRNA levels of breast cancer (MCF-7) cells, and its relationship with cell proliferation and apoptosis. Cytotoxic activity of ethanolic propolis extract (EEP) was evaluated using MTT assay. Mechanisms involved in the cytotoxic action of Turkish propolis in MCF-7 cells were investigated with regard to apoptosis and cell cycle using flow cytometry and western blot. Mitochondrial membrane potential (MMP) were evaluated by spectrofluorometric method. miRNA levels were detected by qRT-PCR method. EEP exhibited selective toxicity against MCF-7 cells compared to normal fibroblast cells. EEP increased the cell cycle arrest at the G1 phase. EEP elevated the apoptotic cell death through increasing pro-apoptotic protein levels (p21, Bax, p53, p53-Ser46, and p53-Ser15), decreasing MMP and altering the expression levels of specific tumor suppressors (miR-34, miR-15a, and miR-16-5p) and oncogenic (miR-21) miRNAs. These data support that Turkish propolis may be evaluated as a potential natural agent for new anticancer drugs in future.